2022
DOI: 10.1136/annrheumdis-2021-221788
|View full text |Cite
|
Sign up to set email alerts
|

Response to SARS-CoV-2 vaccination in systemic autoimmune rheumatic disease depends on immunosuppressive regimen: a matched, prospective cohort study

Abstract: ObjectiveTo assess the humoral response to messenger RNA (mRNA) vaccine of patients with systemic autoimmune rheumatic disease (SARD) and the effect of immunosuppressive medication in a matched cohort study.MethodsPatients with SARD were enrolled and matched 1:1 for sex and age with healthy control (HC) subjects. Differences in humoral response to two doses of an mRNA vaccine in terms of seroconversion rate (SCR) and SARS-CoV-2 antibody level between the two groups and the impact of treatment within patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 34 publications
4
23
0
1
Order By: Relevance
“…Participants with autoimmune diseases usually obtain immunosuppressive drugs. Thus, this finding can be considered consistent with other reports, showing significantly lower antibody response after vaccination among participants with immunosuppression [ 9 , 17 , 18 ] and underlining the potential negative effect of immunosuppressive drugs in this context [ 8 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Participants with autoimmune diseases usually obtain immunosuppressive drugs. Thus, this finding can be considered consistent with other reports, showing significantly lower antibody response after vaccination among participants with immunosuppression [ 9 , 17 , 18 ] and underlining the potential negative effect of immunosuppressive drugs in this context [ 8 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the study by Frey et al , patients on DMARD monotherapy had higher antibody titres than those on combination therapy 5. A recent study by Mandl et al also showed that treatment with GCs in combination with other treatments had a negative impact on the seroconversion rate and the overall antibody level following vaccination 26…”
Section: Discussionsupporting
confidence: 66%
“…Although many patients with IMID mount adequate serological responses to vaccination after 2 doses of an mRNA vaccine, a proportion of patients with IMID show reduced responses compared with healthy controls (7)(8)(9)(10)(11)(12)(13)(14), as confirmed in recent meta-analyses (15,16). Patients receiving glucocorticoids, methotrexate (MTX), mycophenolate, anti-TNF, and B cell-depleting therapy may have attenuated serological responses to COVID-19 vaccines (7,11,13,15,(17)(18)(19)(20)(21)(22)(23)(24). Moreover, 2 recent studies showed that patients on anti-TNF therapy have greater waning of humoral immunity compared with healthy controls (13,21).…”
Section: Introductionmentioning
confidence: 91%